2010
DOI: 10.1103/physrevlett.104.186403
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Spin Hall Effect from First Principles

Abstract: We present an ab initio description of the spin Hall effect in metals. Our approach is based on density functional theory in the framework of a fully relativistic Korringa-Kohn-Rostoker method and the solution of a linearized Boltzmann equation including the scattering-in term (vertex corrections). The skew scattering mechanism at substitutional impurities is considered. Spin-orbit coupling in the host as well as at the impurity atom and the influence of spin-flip processes are fully taken into account. A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
223
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(236 citation statements)
references
References 25 publications
11
223
1
1
Order By: Relevance
“…The estimated D is only weakly dependent on the atomic number Z and falls in the range of 15 ± 2.3 meV for CVDG and EPG decorated with Cu adatoms and 18±2 meV for EPG decorated with Au adatoms. Note that similar to metallic thin films such a weak dependence of Z is expected 42 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The estimated D is only weakly dependent on the atomic number Z and falls in the range of 15 ± 2.3 meV for CVDG and EPG decorated with Cu adatoms and 18±2 meV for EPG decorated with Au adatoms. Note that similar to metallic thin films such a weak dependence of Z is expected 42 .…”
Section: Discussionmentioning
confidence: 97%
“…With respect to the absence of a strong Z dependence, it is important to note that a large SOC at the impurity site is not the only criteria that can give rise to a large SHE. A strong perturbation of the potential at the impurity site can become equally important 42 . Indeed, in both CVD and EPG, the perturbation of the potential-due to the presence of metallic adatom clusters-is large and thus is likely the dominant mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…And the calculated SHCs 32,33 are found to agree well with the corresponding experimental values in many metals such as Al 35 , Pt 36,37 , Au and Pd 38 , suggesting that the intrinsic SHE is dominant in the high resistivity regime in pure metals. Nonetheless, recent experimental 39,40 and theoretical [41][42][43][44][45] studies showed that certain impurities could also give rise to large SHE in impure metals. However, the SHE in ferromagnets remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…For materials with impurities or disorder, extrinsic contributions to the AHE also exist, which can be described within density-functional theory. 5,6 Nevertheless, the intrinsic contribution is often dominating in itinerant ferromagnets with moderate resistivity. 2 Since the intrinsic anomalous Hall conductivity (AHC) is determined by the electronic structure of a pristine crystal [Eq.…”
Section: Introductionmentioning
confidence: 99%